Pola Kepekaan Candida krusei Isolat Jakarta terhadap Flukonazol - Fatril, Ayu Eka; Adawiyah, Robiatul; Wahyuningsih, Retno (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Introduction: Candida krusei inhabit the human body as saprophyte but can turn into pathogen and causes mycosis. Candida krusei usually primarily resistant to fluconazole but laboratory data in Jakarta has different results. We found fluconazole-susceptible isolates which encouraged us to do prospective studies using the different isolates of C. krusei.Method: The study was conducted in 2019-2020 in the Laboratory of Parasitology, Faculty of Medicine, Universitas Indonesia. The total of 15 C. krusei isolates were tested by disc diffusion method. Before being tested, the isolates were refreshed and purified to obtain a single colony. Result: The isolates used, derived from many clinical samples i.e. stool, sputum, broncho-alveolar lavage (LAB) and one isolate isolated from lung abscess. The result of susceptibility test showed nine fluconazole-resistant isolates, one intermediate isolate and five fluconazole-susceptible isolates. Conclusion: It can be concluded, in vitro, some Candida krusei isolates in Jakarta are susceptible to fluconazole.